JÑANA MARGA YOGA, PHILOSOPHY OF LIFE IN THE SRICPT OF SÊRAT BHAGAWAD GITA - Doni Dwi Hartanto; Endang Nurhayati (Jurnal Penelitian Humaniora, 2017)
This research aimed to interpretate Jñana Marga Yoga philosophy of life and interpretate the doctrine of Jñana Marga Yoga in the manuscript of Sêrat Bhagawad Gita. The research used philology and descriptive methods. Philological method was carried out in three stages, namely the transliteration, editing, and translation of text. Descriptive method was used to interpretate the philosophy of life and the value of the theaching of the text. The source of the data was a manuscript of Sêrat Bhagawad Gita. Data was analyzed using descriptive analysis. Validation of data used semantic validity and reliability (intrarater and interrater). The result of this research are as follows. (1) The philosophy of life from Jñana Marga Yoga is (a) seeing the glory of God, (b) the way of perfection, (c) the science of karma, (d) the science of yadnya, (e) the science of wisdom. (2) Jñana Marga Yoga is the way to achieve the perfection of life with the knowledge of wisdomFALSAFAH HIDUP JÑANA MARGA YOGA DALAM NASKAH SÊRAT BHAGAWAD GITAPenelitian ini bertujuan untuk melakukan interpretasi falsafah hidup Jñana Marga Yoga dan interpretasi ajaran Jñana Marga Yoga dalam naskah Sêrat Bhagawad Gita. Metode penelitian meliputi dua tahap, yaitu metode filologi dan metode deskriptif. Metode filologi dilakukan dengan tiga tahapan, yaitu transliterasi, suntingan, dan terjemahan teks. Metode penelitian deskritif digunakan dalam interpretasi ajaran dan falsafah hidup teks. Sumber data penelitian ialah naskah berjudul Sêrat Bhagawad Gita. Analisis dilakukan dengan analisis deskriptif. Validitas dan reliabilitas yang digunakan ialah validitas semantik dan reliabilitas (intrarater dan inerrater). Hasil penelitian adalah sebagai berikut: (1) falsafah hidup Jñana Marga Yoga yaitu (a) melihat kemuliaan Tuhan, (b) jalan kesempurnaan, (c) ilmu tentang karma, (d) ilmu tentang yadnya, (e) ilmu kebijaksanaan; dan (2) Jñana Marga Yoga merupakan jalan yang ditempuh untuk mencapai kesempurnaan hidup dengan jalan ilmu kebijaksanaan